Answer:
Y= -12
Step-by-step explanation:
6(y + 7) = 2(y - 3)
6y+42=2y-6
4y+42=-6
4y=-48
y=-12
C=150•(3/5)•5
C=450
So if she ate the whole bag, she’d eat 450 calories.
Answer:
<em><u>2</u></em><em><u>3</u></em><em><u>.</u></em><em><u>E</u></em>
Step-by-step explanation:
<em><u>please click the heart and rate excellent and brainleist to </u></em><em><u>☻</u></em><em><u>❤</u></em><em><u>☺️</u></em><em><u>☺️</u></em><em><u>❤</u></em><em><u>☻</u></em>
Answer:
3/4 - 5/12
Step-by-step explanation:
first you make the demoninators the same so 3*4=12
and if you *3 you do it to the numerator
so its 9/12-5/12
the unsimplified fraction is 4/12
if wanted simplified version its 1/3